2022
DOI: 10.1111/liv.15199
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inhibition of PPARα ameliorates CLA‐induced hypercholesterolemia via hepatic cholesterol biosynthesis reprogramming

Abstract: Background & Aims: Disruption of lipid metabolism is largely linked to metabolic disorders, such as hypercholesterolemia (HCL) and liver steatosis. While cholesterol metabolic re-programmers can serve as targets for relevant interventions. Here we explored the dietary conjugated linoleic acids (CLA)-induced HCL in mice and the molecular regulation behind it.Methods: A high dose of CLA supplementation in the diet was used to induce HCL in mice and was found to cause a hyper-activated cholesterol biosynthesis pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Total RNA extracted from IPI-2I cells using TRIzol Reagent (Takara Biotech, Dalian, China) was reverse-transcribed into cDNA using HiScript ® II Q Select R.T. SuperMix (Vazyme, Nanjing, China) according to the manufacturer’s instructions and previous report ( 12 , 13 ). qRT-PCR analysis was performed by an ABI StepOne Plus Real-Time PCR System (Applied Biosystems, CA, USA) using AceQ ® qPCR SYBR Green Master Mix (Vazyme, Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA extracted from IPI-2I cells using TRIzol Reagent (Takara Biotech, Dalian, China) was reverse-transcribed into cDNA using HiScript ® II Q Select R.T. SuperMix (Vazyme, Nanjing, China) according to the manufacturer’s instructions and previous report ( 12 , 13 ). qRT-PCR analysis was performed by an ABI StepOne Plus Real-Time PCR System (Applied Biosystems, CA, USA) using AceQ ® qPCR SYBR Green Master Mix (Vazyme, Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
“…Cold PBS was used to wash the liver tissues randomly selected from the PEDV-infected and uninfected piglets. In order to prepare the total RNA for RNA-seq, Illumina Tru-Seq RNA Sample Preparation Kit was used as previously described [ 31 ]. Firstly, the quality of libraries should be eligible, and an Agilent 2100 Bioanalyzer was used to check it.…”
Section: Methodsmentioning
confidence: 99%
“…As in a previous description [ 31 , 35 ], ChIP-qPCR was performed with the following modifications. In short, 1% formaldehyde was used to cross-link liver tissues for 5 min, then the fixing buffer containing 100 mmol/L NaCl, 50 mmol/L Hepes-KOH, 1 mmol/L EDTA, and 0.5 mol/L EGTA was used for pulverizing and resuspending.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, ectopic RORγ overexpression performed similar effects with those of the agonists possibly via epigenetically recruited histone active marks H3K27ac. A recent study also revealed RORγ as an essential mediator in facilitating the interaction of PPARα and SREBP2 and in controlling the cholesterol biosynthesis genes transcription ( 62 ). This new complex of “PPARα-RORγ-SREBP2” explored a new mechanism on cholesterol reprogramming in a context and cell-type-specific manner, which would be beneficial for the invention of therapeutic strategy for MetS and related metabolic diseases.…”
Section: Rorγ Is Closely Linked To Sterols' Metabolismmentioning
confidence: 99%
“…This new complex of “PPARα-RORγ-SREBP2” explored a new mechanism on cholesterol reprogramming in a context and cell-type-specific manner, which would be beneficial for the invention of therapeutic strategy for MetS and related metabolic diseases. Indeed, PPARα plays a novel role in MetS because of the changed functions induced by RORγ in different scenarios, suggesting the complicated crosstalk among these NRs ( 62 , 63 ). Given the fact that LXRs modulate the cholesterol intake and efflux by the key enzymes such as LDLR and ABCA1/G1, it is suggested that a diminished RORγ availability is associated with decreased cholesterol production in response to LXR activation ( 53 , 55 , 64 ).…”
Section: Rorγ Is Closely Linked To Sterols' Metabolismmentioning
confidence: 99%